2014
DOI: 10.1007/s00167-014-3200-5
|View full text |Cite
|
Sign up to set email alerts
|

Three different cruciate-sacrificing TKA designs: minor intraoperative kinematic differences and negligible clinical differences

Abstract: III.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
20
1

Year Published

2015
2015
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(24 citation statements)
references
References 41 publications
3
20
1
Order By: Relevance
“…Many studies have compared between TKAs with an UC insert and other design inserts. 9,11 14,31,32 In terms of clinical outcomes, most of studies demonstrated similar results of UC design TKA with PS or CR, it is consistent with our study results. Multiple factors include geometry, implant size, type of insert, PCL integrity, and gap balancing are associated with AP instability in TKAs.…”
Section: Discussionsupporting
confidence: 92%
“…Many studies have compared between TKAs with an UC insert and other design inserts. 9,11 14,31,32 In terms of clinical outcomes, most of studies demonstrated similar results of UC design TKA with PS or CR, it is consistent with our study results. Multiple factors include geometry, implant size, type of insert, PCL integrity, and gap balancing are associated with AP instability in TKAs.…”
Section: Discussionsupporting
confidence: 92%
“…Casino et al [5] performed intraoperative kinematic assessments of mobile PS TKA and reported paradoxical anterior translation of the femur that was similar to our result, but there was no internal rotation of the femur. In addition, the pattern of axial rotation of mobile UC and PS TKA in Bignozzi et al's study was different from that in both Casino et al's and our study [3, 5]. Different kinematic patterns among these studies might result from a different navigation system or method of passive motion.…”
Section: Discussioncontrasting
confidence: 81%
“…Despite the kinematic differences, studies have found equivalent clinical outcomes between PS TKA and UC inserts. 47,49,50,55,56 Some studies have also shown that UC inserts have comparable clinical outcomes to cruciate retaining TKA. 54,5759…”
Section: Ultracongruent Insertsmentioning
confidence: 99%